Persistent vs Recurrent Cushing’s Disease Diagnosed Four Weeks Postpartum - Leena Shah; Emily V. Nosova; Joshua B. Bederson; Khadeen Christi Cheesman (Case Reports in Endocrinology)
Background. Cushing’s disease (CD) recurrence in pregnancy is thought to be associated with estradiol fluctuations during gestation. CD recurrence in the immediate postpartum period in a patient with a documented dormant disease during pregnancy has never been reported. Case Report. A 30-year-old woman with CD had improvement of her symptoms after transsphenoidal resection (TSA) of her pituitary lesion. She conceived unexpectedly 3 months postsurgery and had no symptoms or biochemical evidence of recurrence during pregnancy. After delivering a healthy boy, she developed CD 4 weeks postpartum and underwent a repeat TSA. Despite repeat TSA, she continued to have elevated cortisol levels that were not well controlled with medical management. She eventually had a bilateral adrenalectomy. Discussion. CD recurrence may be higher in the peripartum period, but the link between pregnancy and CD recurrence and/or persistence is not well studied. Potential mechanisms of CD recurrence in the postpartum period are discussed below. Conclusion. We describe the first report of recurrent CD that was quiescent during pregnancy and diagnosed in the immediate postpartum period. Understanding the risk and mechanisms of CD recurrence in pregnancy allows us to counsel these otherwise healthy, reproductive-age women in the context of additional family planning.